Yield and economic analysis of rice (Oryza sativa) under different inorganic fertilizers in conjunction with FYM - Sheikh, T.A.; Baba, Z.A.; Haq, Ansar ul; Bhat, R.A.; Singh, Ummed (Annals of Agricultural Research, 2014)
The experiment was conducted for two consecutive years (2008 and 2009) at Shalimar on a silty clay loam soil, low in available nitrogen and sulphur, medium in available phosphorus and potassium. The experiment comprising of 27 treatment combinations viz., three FYM levels (10, 20 and 30 t ha-1), three phosphorus levels (60, 80 and 100 kg P2O5 ha-1) and three sulphur levels (20, 40 and 60 kg S ha-1), was laid out in a split plot design with three replications. Application of 30 t FYM ha-1 being at par with 20 t FYM ha-1 resulted in significantly higher grain yield of rice over 10 t FYM ha-1 besides, recorded significant increase in the yield attributes with concomitant improvement in the growth characters as well. Phosphorus application beyond 60 kg ha-1 had no significant influence on the grain yield and yield attributes. The yield and yield attributes of rice responded significantly up to 40 kg S ha-1 compared to 20 kg S ha-1. The highest benefit: cost ratio of Rs. 1.65 and net profit of Rs. 65359.8 was recorded with treatment combination of 20 t FYM ha-1, 60 kg P2O5 ha-1 and 40 kg S ha-1, hence the treatment combination is recommended for obtaining higher profitability of rice under Kashmir valley.